Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Pegawai Pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Jambi - Arman Syafa’at; Andri Devita (Universitas Batanghari, 2021)
The research entitled Effect Of The Work Environment And Work Load On Employee Performance In The Jambi Provincial Regional Financial And Assets Management Agency uses primary data which is presented in the form of a sample size for employees at the Regional Financial and Asset Management Agency of Jambi Province, namely Civil Servants who are 108 employees while the sample for honorary employees is 21 employees, so the total sample of employees is 129 people. The results showed that 1). Work Environment Variable (X1) Respondents' answers to the work environment variable averaged 3.65 or 73.01% with the criteria for a good work environment. Thus, it can be stated that